International Coconut Genetic Resources Network (COGENT): Its history and achievements - Pons Batugal (International Coconut Community, 2005)
The International Coconut Genetic Resources Network (COGENT) is a global research network organized by the International Plant Genetic Resources Institute (IPGRI) in 1992 with support from member countries, the Consultative Group on International Agricultural Research (CGIAR), partner institutions, donor agencies, and by regional and international development organizations. In the last 12 years, COGENT has been fully operational with 38 member coconut producing countries in five regions (South Asia; Southeast and East Asia; South Pacific; Africa and the Indian Ocean; and Latin America and the Caribbean). It has successfully developed and disseminated to coconut breeders and curators worldwide the International Coconut Genetic Resources Database (CGRD). The CGRD contains characterization data and some pictures of 1,416 accessions which are conserved by national programmes in 28 sites in 23 countries. To further secure conserved germplasm, a COGENT multi-site International Coconut Genebank has been established to conserve 200 important accessions in each region. Coconut varieties with multi-purpose uses are being identified, documented and promoted. The performance of promising 38 high-yielding hybrids are being evaluated in a multilocation trial involving four African and three Latin America/Caribbean countries to identify suitable varieties and hybrids for resource-poor farmers. Farmers’ varietal preferences in 15 countries are being evaluated. Diversity-linked income-generating activities are being used as a strategy to promote in situ and on-farm conservation and germplasm utilization have been initiated in 15 countries. Protocols for in vitro embryo culture, cryopreservation, morphometric and molecular marker-based methods for locating and characterizing diversity; pest risk assessment and germplasm health management are being developed, tested and upgraded. Strategies and techniques for farmer participatory research, collecting, characterization and ex situ and in situ conservation are being refined. To strengthen the coconut research capability of COGENT member countries, the COGENT Secretariat and IPGRI have organized 39 country need assessment missions and conducted 41 workshops and meetings involving 994 coconut researchers to share information and technologies, discuss issues and common problems and opportunities and how to address them; conducted 40 training courses involving 765 participants from 41 countries; supported 274 research and training/capacity building activities in 30 countries; and led the establishment of the Global Coconut Research for Development Programme (PROCORD). IPGRI and COGENT's current priority involves the further promotion of more effective conservation and use of coconut genetic resources, both regionally and globally.